Psychosocial Safety Climate Moderates the Effect of Demands of Hospital Accreditation on Healthcare Professionals: A Longitudinal Study - Alshamsi, Amna I.; Santos, Angeli; Thomson, Louise (Frontiers in Health Services, 2022)
Hospital accreditation has been studied comprehensively, yet few studies have observed its impacts on the burnout and work engagement levels of frontline healthcare professionals (HCPs). With a sample of 121 HCPs working in the United Arab Emirates’ public hospitals, this study used a two-wave, cross-lagged panel design to examine the direct effects of job demands and job resources during hospital accreditations on burnout and work engagement and the moderating roles of psychosocial safety climate (PSC) on burnout and work engagement three months after accreditation. The data were analyzed using moderated structural equation modeling. As expected, we found that job demands (i.e., accreditation demands) had a direct effect on burnout, while job resources (i.e., social support) predicted work engagement. PSC moderated both relationships; however, it was not able to directly predict burnout or work engagement. Findings from this study show a positive relationship between accreditation demands and HCPs’ health. Future research needs to examine the link between PSC and job demands-resources concepts before and after hospital accreditation more closely by using multiple time points to assess the causality relationships between predictor and outcome variables.